2022
DOI: 10.12890/2022_003528
|View full text |Cite
|
Sign up to set email alerts
|

Paxlovid with Caution: Novel Case of Paxlovid-Induced Tacrolimus Toxicity in a Cardiac Transplant Patients

Abstract: Tacrolimus is commonly used as a prophylactic against acute rejection in transplant patients. Tacrolimus toxicity has numerous presentations that have been well documented in the literature and can be induced by a wide variety of agents. We present a novel case of tacrolimus toxicity in a cardiac transplant patient induced by outpatient treatment for COVID-19 pneumonia with ritonavir-nirmatrelvir, which was successfully treated with phenytoin therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…The median time for the tacrolimus concentration to return to baseline levels after holding NR was 8 (IQR, 7–12) days. Notably, in two case reports ( 20 , 21 ), rifampin and phenytoin were used to accelerate tacrolimus metabolism, resulting in a rapid decline in therapeutic levels.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The median time for the tacrolimus concentration to return to baseline levels after holding NR was 8 (IQR, 7–12) days. Notably, in two case reports ( 20 , 21 ), rifampin and phenytoin were used to accelerate tacrolimus metabolism, resulting in a rapid decline in therapeutic levels.…”
Section: Resultsmentioning
confidence: 99%
“…Fortunately, most transplant patients recovered after prompt drug withdrawal and hospital care. Notably, two studies have reported that phenytoin and rifampicin can be used to accelerate tacrolimus metabolism and excretion, resulting in a significant reduction in tacrolimus concentration ( 20 , 21 ). Phenytoin and rifampin are potent inducers of CYP3A4 and P-glycoprotein, which can quickly reduce tacrolimus levels as antidotes ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nirmatrelvir/ritonavir could also exhibit potential life-threatening interactions in individuals on immunosuppressants which are mainly metabolized by CYP3A. As one immunosuppressant metabolized by CYP3A, tacrolimus have been reported to have significant interactions with nirmatrelvir/ritonavir in some cases, most were from patients with solid organ transplant ( Berar et al, 2022 ; Cadley et al, 2022 ; Kwon et al, 2022 ; Prikis and Cameron, 2022 ; Shah et al, 2022 ; Chen et al, 2023 ; Modi et al, 2023 ; Sindelar et al, 2023 ; Snee et al, 2023 ; Young et al, 2023 ; Zaarur et al, 2023 ). These patients presented with different symptoms including nausea, vomiting, fatigue, weakness, loss of appetite, abdominal pain, slowed speech, and peripheral neuropathy after they took nirmatrelvir/ritonavir without discontinuing tacrolimus.…”
Section: Discussionmentioning
confidence: 99%
“…Devresse and others used a standard management strategy of tacrolimus dose adaptation (discontinuation of tacrolimus 12 h before the start of nirmatrelvir/ritonavir) for a case series of 14 kidney transplant recipients with COVID-19, no acute kidney injury was observed during the treatment course and tacrolimus was resumed 6 days later ( Devresse et al, 2022 ). When patients present toxic symptoms and/or signs, tacrolimus must be discontinued and CYP inducers (phenytoin or rifampin) can be used to reverse the toxicity, which has been reported by some researchers ( Cadley et al, 2022 ; Kwon et al, 2022 ; Shah et al, 2022 ; Sindelar et al, 2023 ; Snee et al, 2023 ; Xiong et al, 2023 ). However, the use of CYP inducers might compromise the effectiveness of nirmatrelvir/ritonavir treatment by increasing the metabolism of nirmatrelvir.…”
Section: Discussionmentioning
confidence: 99%